ANALISIS PENERAPAN PSAK NO.14 DALAM METODE PENILAIAN DAN PENCATATAN PERSEDIAAN PADA KUD KANDANGAN, SIMALUNGUN - Nuraini, Nuraini; Zahari, Zahari; Mulyani, Sri (Jurnal Manajemen Akuntansi dan Ilmu Ekonomi, 2025)
This study aims to ascertain whether the application of the method of valuation and recording of KUD Kandangan inventory is appropriate or not. This research was conducted at KUD Kandangan which is located in Kandangan Village, Bosar Bayu, Pematang Bandar District, Siamlungun Regency, North Sumatra. The method used in this research is a qualitative method that the data is in the form of recording, research, measurement and disclosure of inventory in KUD Kandangan with PSAK No.14 about Inventory. For data collection using observation with a direct review of the company, interviews with the company and documentation in the form of documents or financial statements and accounting records related to research problems. The results of this study provide that every trading company requires inventory of trade goods to be sold. In the method of recording the inventory of trade goods in KUD Kandangan Simalungun has done inventory of goods, especially with the perpetual method. As for the FIFO (First In, First Out) method used for valuation of merchandise inventory. Disclosure of existing inventory in KUD Kandangan Simalungun can be presented in accordance with PSAK No.14 in the financial statements, especially the income statement and statement of financial position.